The relationship of inclusive climate and peers' attitude on children with disabilities in China: A mediating role of empathy - Fu, Wangqian; Xiao, Yawen; Yin, Cui; Zhou, Tianqi (Frontiers in Psychology, 2022)
Objective Peer attitude towards children with disabilities can significantly impact on the successful implementation of inclusive education. The current study examined the attitude of Chinese students toward peers with disabilities in relation to inclusive climate and empathy. Method A total of 392 typically developing students (aging from 10 to 17 years old, with average age of 12.7) in primary and middle schools participated in the study by reporting the Inclusive Climate Scale, Peers Attitude to Students with Disabilities Scale, and Balanced Emotional Empathy Scale. Results We found that students held a neutral attitude to peers with disabilities, and girls were more acceptable than boys. There were positive relationships among inclusive climate, empathy and attitude to classmates with disabilities. The mediation analysis showed that empathy played a partial mediation role between inclusive climate and the peers' attitude towards children with disabilities. Conclusion Implications for improving students' attitude on peers with disabilities were discussed in the paper.